An Increased Long Range Of Drones With A Smartnet System - Zulfadli Pelawi; Hermansyah Alam; Mahrizal Masri; Armansyah, Armansyah (SEAN Institute, 2023)
Smart drones are a type of miniature Unmanned Aerial Vehicle (UAV) or can be translated as an unmanned aircraft which is also commonly called a Drone. Drone categories currently consist of fixed wings (drones that use wings) and multirotor (drones that use more than one motor and without wings). Multirotor drones can use 3 motors, 4 motors, 6 motors and 8 motors. Smart drones have a control system to be able to fly according to the wishes of the operator in Ground Control. Power The range of a smart drone with a manufacturer's control system is limited to 100 meters, thus limiting smart drones from flying further. Changing the control system with a stronger signal transmitter on smart drones can increase the drone's range. This research produced an Ardupilot-based control system to increase the drone's range.